Redefining the digital age: the AI renaissance in human-computer interaction and decision-making - Goyal, Ishita (Review of Artificial Intelligence in Education, 2023)
Objective: This paper aims to explore the concept of AI as a modern-day Renaissance movement, triggered by the proliferation of the internet and advancements in artificial intelligence technologies. It delves into the transformative impact of AI on human-computer interactions and decision-making processes. Results: O’Leary’s (1997) early notion of a Renaissance movement sparked by the internet’s ubiquity finds resonance in the emergence of the AI renaissance. AI technologies such as natural language processing, machine learning, heuristic language processing, and neural networks have integrated into intricate networked computing environments. These technologies facilitate the handling, retrieval, and analysis of vast amounts of data available on the World Wide Web. Given the overwhelming volume of data, direct human analysis has become impractical, necessitating AI-driven support for efficient data utilization. In today’s competitive and tech-driven landscape, the time available for decision-making has diminished, prompting reliance on intelligent agents and delegating decision-making tasks to these digital surrogates. Conclusions: The contemporary AI renaissance signifies a paradigm shift in human-computer dynamics. The convergence of AI technologies with the internet’s vast information landscape has created a symbiotic relationship, redefining traditional computer roles. AI-enabled tools not only manage the deluge of data but also extend decision-making capabilities, optimizing efficiency in an increasingly fast-paced world. This transformative movement transcends conventional computing boundaries and has paved the way for a new era of human-machine interaction.